2014
DOI: 10.4269/ajtmh.14-0369
|View full text |Cite
|
Sign up to set email alerts
|

Brucella Induced Guillain–Barré Syndrome

Abstract: Abstract. Neurobrucellosis is relatively uncommon. In a prospective study of 530 patients with brucellosis, neurologic involvement was reported in only 1.7% of the patients. Unlike Campylobacter jejuni, the commonest infection implicated in Guillain-Barré syndrome, there are very few reports in the literature of Guillain-Barré syndrome in association with brucellosis. Out of 1,028 cases of brucellosis, polyneuritis was reported in only 2 out of 58 patients with neurological involvement. CASE REPORTA 54-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A 26-year-old woman and a 54-year-old man reported a GBS-related Brucella infection with upper and lower limb numbness, muscle weakness, and eye and facial weakness associated with GBS. Both achieved satisfactory results after appropriate immunoglobulin therapy [ 10 , 11 ]. Alanazi et al reported 19 patients with GBS during active brucellosis in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…A 26-year-old woman and a 54-year-old man reported a GBS-related Brucella infection with upper and lower limb numbness, muscle weakness, and eye and facial weakness associated with GBS. Both achieved satisfactory results after appropriate immunoglobulin therapy [ 10 , 11 ]. Alanazi et al reported 19 patients with GBS during active brucellosis in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…The most reported manifestations of neurobrucellosis are meningitis and meningoencephalitis [2]. Neurobrucellosis may also present as myelitis, myelopathy, stroke, paraplegia, radiculoneuritis, intracerebral abscess, epidural abscess, intradural abscess, demyelination, Guillain-Barré syndrome, polyneuritis, and cranial nerve involvement or any combination of these manifestations [3,8,9,10]. Neurobrucellosis affects the second, third, sixth, seventh, and eighth cranial nerves.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Neurobrucellosis is a focal complication of brucellosis affecting both central and peripheral nervous system (PNS) presenting with a variety of signs and symptoms [2]. Neurologic involvement due to brucellosis was reported in 1.7%-10% of the patients with brucellosis [3,4,5]. Neurological complications of brucellosis are divided into two groups.…”
Section: Introductionmentioning
confidence: 99%
“…18 Further, there are reports of patients with GBS who developed the syndrome after infection with Brucella. 19 Other theories argue that the cause of GBS may be because of viral infection, 20 and some even claim that the association may not be related to infection at all. Still, most reports exhibit a negative interplay between infections and demyelination syndromes.…”
mentioning
confidence: 99%
“…In fact, severe axonal degeneration in GBS is more common following C. jejuni infection . Further, there are reports of patients with GBS who developed the syndrome after infection with Brucella . Other theories argue that the cause of GBS may be because of viral infection, and some even claim that the association may not be related to infection at all.…”
mentioning
confidence: 99%